Effect of nanocapsules and extract of Metarhizium anisopliae in inhibiting acetylcholine esterase enzyme in Musca domestica larvae. (Baghdad Science Journal, 2024)
M. domestica is the most important insect that transmit pathogens for diseases in the world. The use of nanotechnology is eco-friendly method in control pests. The study aims to investigate the feasibility of bio-manufacturing nanocapsules of fungal secondary metabolites in order to improve the efficiency of metabolite and assess their inhibitory effect on the acetylcholine esterase enzyme in housefly larvae. An equal mixture of organic solvents, ethyl acetate and dichloromethane, was used to extract the metabolic products of the fungus M. anisopliae, (PEG4000) and chitosan was used in the preparation of nanocapsules. The results of the DLS granular size assay showed that the size of the extract particles and the size of the chitosan and (PEG 4000) nanocapsules were 610, 217 and 188 nm, respectively. The SEM images showed that the diameter of the extract and the nanocapsules chitosan and polyethylene glycol 4000 reached a rate 547.5, 17.8 and 26.2 nm, respectively. The FTIR showed that the extract of the second products of the fungus contains functional groups like: alkynes and alkenes, amines, carboxyl and aromatic groups, while the presence of groups of phenols, alcohol, amines, alkenes, and alkyl halides was recorded for nanocapsules of chitosan and PEG. The results showed that the extract of fungal metabolic and nanocapsules has an inhibitory effect on acetylcholinesterase enzyme and reached the highest inhibition rate 53.2 ,36.3,18.2% when treated with nanocapsules PEG at a concentration 500 ppm, extract of fungal metabolites at a concentration 50,000 ppm, chitosan nanocapsules at a concentration 500 ppm respectively. It is clear that acetylcholinesterase inhibition is one of the mechanisms of fungi metabolic action and the nanocapsules prepared from them.